1997
DOI: 10.1021/jf970405b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baking and Frying on the Fumonisin B1 Content of Corn-Based Foods

Abstract: Fumonisins are mycotoxins produced primarily by Fusarium moniliforme and Fusarium proliferatum in corn. Fumonisins have been implicated as the causal agents in a variety of animal diseases and are epidemiologically linked to the high incidence of human esophageal cancer in some regions of the world. Little is known about the effects of common processing methods on the fumonisin content of food. The objective of this study was to determine the effects of baking and frying on the stability of fumonisin B1 (FB1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 34 publications
5
52
1
2
Order By: Relevance
“…The percent of FB 1 retained in muffins baked at 175°C (83.7 ± 3.5%) was slightly greater than that in muffins baked at 200°C (72.4% ± 5.9%). As compared to the data reported here, the higher FB 1 retention obtained by Jackson (1997) could be due to the lower baking temperatures used.…”
Section: Bakingcontrasting
confidence: 62%
See 2 more Smart Citations
“…The percent of FB 1 retained in muffins baked at 175°C (83.7 ± 3.5%) was slightly greater than that in muffins baked at 200°C (72.4% ± 5.9%). As compared to the data reported here, the higher FB 1 retention obtained by Jackson (1997) could be due to the lower baking temperatures used.…”
Section: Bakingcontrasting
confidence: 62%
“…FB 1 and FB 2 retentions of 36 and 28% were reported for muffins baked at 220°C for 25 min. Baking of maize meal muffins at 175 and 200°C by Jackson et al (1997) resulted in small but statistically significant (p<0.005) losses of FB 1 . The percent of FB 1 retained in muffins baked at 175°C (83.7 ± 3.5%) was slightly greater than that in muffins baked at 200°C (72.4% ± 5.9%).…”
Section: Bakingmentioning
confidence: 93%
See 1 more Smart Citation
“…41 In similar work, Castelo and co-workers observed that the roasting of maize meal samples which were either artificially (5 µg g −1 of FB 1 ) or naturally contaminated, at 218…”
Section: Fumonisinsmentioning
confidence: 91%
“…Although no study has reported an increase in mycotoxin levels after frying in the literature, masa fried at 140-170 o C gave no reduction in fumonisins [19]. Bullerman and Bianchini [20] also suggested that dry heat appears to be more destructive to mycotoxins than moist heat, which was used in this study.…”
Section: Discussionmentioning
confidence: 58%